2015
DOI: 10.1186/s12887-015-0510-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of hospital versus home based therapy with oral amoxicillin for severe pneumonia in children aged 3 – 59 months: The IndiaCLEN Severe Pneumonia Oral Therapy (ISPOT) Study

Abstract: BackgroundPneumonia is the leading cause of child mortality under five years of age worldwide. For pneumonia with chest indrawing in children aged 3–59 months, injectable penicillin and hospitalization was the recommended treatment. This increased the health care cost and exposure to nosocomial infections. We compared the clinical and cost outcomes of a seven day treatment with oral amoxicillin with the first 48 h of treatment given in the hospital (hospital group) or at home (home group).MethodsWe conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 13 publications
(12 reference statements)
2
29
0
Order By: Relevance
“…In the IndiaCLEN multi-centre trial (NCT01386840), the safety and efficacy of oral amoxicillin for severe pneumonia at home or in hospital were compared [ 28 ]. This open-label, multi-centre, prospective, two-arm, randomised clinical trial in children aged 3–59 months with severe pneumonia aimed to determine the differences in treatment failure between a 7-day course of oral amoxicillin for the first 48 h in hospital and being sent home on the same treatment after enrolment.…”
Section: Resultsmentioning
confidence: 99%
“…In the IndiaCLEN multi-centre trial (NCT01386840), the safety and efficacy of oral amoxicillin for severe pneumonia at home or in hospital were compared [ 28 ]. This open-label, multi-centre, prospective, two-arm, randomised clinical trial in children aged 3–59 months with severe pneumonia aimed to determine the differences in treatment failure between a 7-day course of oral amoxicillin for the first 48 h in hospital and being sent home on the same treatment after enrolment.…”
Section: Resultsmentioning
confidence: 99%
“…This criteria was removed as a referral sign in the revised 2014 WHO IMCI chart booklet [ 8 ] following controlled low-mortality trials that indicated chest indrawing episodes could be managed at home without increased risk [ 25 , 26 ], and Malawi made this change too in 2018. Since then, 3 other randomised trials—one each in India, Kenya, and Malawi—have demonstrated that chest indrawing pneumonia can be treated with oral amoxicillin on an outpatient basis [ 27 29 ]. However, for CHWs, chest indrawing remains a referral sign.…”
Section: Discussionmentioning
confidence: 99%
“…Previous antibiotic treatment and household air pollution reduction trials have failed to show an association between pneumonia and the exposure of interest. 10,11,[104][105][106][107][108][109] Many of these trials used the WHO definition of pneumonia, which is solely based on clinical symptoms and signs, is highly sensitive, but also has a low specificity. Although effective in informing treatment guidelines that largely reduced childhood mortality, 21,32 use of the WHO definition could lead to reduced effect size and study power in field trials.…”
Section: Discussionmentioning
confidence: 99%